The need for more holistic immune profiling in next-generation SARS-CoV-2 vaccine trials - Murphy, Robert L.; Paramithiotis, Eustache; Sugden, Scott; Chermak, Todd; Lambert, Bruce; Montamat-Sicotte, Damien; Mattison, John; Steinhubl, Steve (Frontiers in Immunology, 2022)
The first-generation of anti-SARS-CoV-2 vaccines were highly successful. They rapidly met an unforeseen emergency need, saved millions of lives, and simultaneously eased the burden on healthcare systems worldwide. The first-generation vaccines, however, focused too narrowly on antibody-based immunity as the sole marker of vaccine trial success, resulting in large knowledge gaps about waning vaccine protection, lack of vaccine robustness to viral mutation, and lack of efficacy in immunocompromised populations. Second-generation clinical trials must address these gaps by evaluating a broader range of immune markers, including those representing cell-mediated immunity to ensure the most protective and long-lasting vaccines are brought to market